KUALITAS PELAYANAN BUS RAPID TRANSIT (BRT) TRANS SEMARANG TERHADAP KEPUASAN PELANGGAN (Koridor IV Cangkiran – Bandara A. Yani) - Yunika Trinandika; Mochammad Mustam; Rihandoyo Rihandoyo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
A quality service rated if already meet the satisfaction of its customers , if customers feel satisfied then these services could be said that quality. The rapid growth of Semarang city increase transportation necessity. The government of semarang city hold public transport based on fast with the fare affordable, such as bus rapid transit (BRT) Trans Semarang but BRT Trans Semarang service corridor IV is still not optimal. There are many problems in several factors like time for a long wait for the bus, the officers in shelters, the complete facilities and infrastructure, lack of priorities for users who have special needs and the officer’s behavior to passengers. The author using a technique quantitative data analysis using mean to find the average score the implementation level service performance and the average level of the interests of service. There are 15 service element used as a material assessment of performance and the interests of service are the clarity, the ability of officers, the responsibility of the officers, discipline of officers, courtesy and kindness officers, procedures, the convenience of the environment, the terms of service, security, get the service of justice, the completeness of facilities and infrastructure, the certainty of cost, the speed of service, the schedule of certainty and reasonable costs. The average of service performance element is 2.80 so that an element that has the value of the average under that needs to be improved. While the average of interest element is 3,84 so that an element that has the value of the average above that need attention for its performance. Based on this research result that there are still some element of the services need to be the main priority in the repair because it is still poorly and is important that the courtesy and kindness comfort environment, the security services, fairness to get the service, the complete facilities and infrastructure and the service schedule.